Formulation and Quality Evaluation of Enriched Balanced Weaning Food at Low Cost - Pulami, Bhim Prasad; Katawal, Surendra (Journal of Food Science and Technology Nepal, 2013)
Due to wide spread poverty, low income and non-availability of nutritious foods there are rampant of nutritional disorders such as protein energy malnutrition (PEM), anemia, vitamin-A deficiency, iodine deficiency disorder among preschool children in developing countries. Main purpose of the study is to formulate low cost supplementary weaning food from locally available raw materials. Based on the sensory evaluation, formula-I was preferred as a best sample (p<0.05). Chemical analysis of formula-I had been performed and found to be 2.02% moisture, 11.72% crude protein, 20.58% crude fat, 3.11% total ash, 2.69% crude fiber, 59.88% carbohydrate (by difference), 471 Kcal/100 g energy (calculated), 870.15 mg/100g vitamin A (âcarotene; calculated), 11.86mg/100g iron, 275mg/100g calcium, 23.55mg/100g ascorbic acid, 35.6μg/100g iodine and 55% water absorbing capacity. The costing revealed the retail product price per kg as NRs. 71.20. J. Food Sci. Technol. Nepal, Vol. 6 (118-121), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8273